2011
DOI: 10.1128/iai.01146-10
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gastric Epithelial Cell-Derived Transforming Growth Factor β in Reduced CD4 + T Cell Proliferation and Development of Regulatory T Cells during Helicobacter pylori Infection

Abstract: Gastric epithelial cells (GECs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 34 publications
2
34
0
3
Order By: Relevance
“…For GEC:T cells co-culture experiments naïve CD4 + T cells were isolated from peripheral blood as previously described (17). Briefly, heparinized venous blood samples were collected from healthy volunteers negative for H. pylori (IRB-approved protocol 06-122 at the University of Texas Medical Branch).…”
Section: Methodsmentioning
confidence: 99%
“…For GEC:T cells co-culture experiments naïve CD4 + T cells were isolated from peripheral blood as previously described (17). Briefly, heparinized venous blood samples were collected from healthy volunteers negative for H. pylori (IRB-approved protocol 06-122 at the University of Texas Medical Branch).…”
Section: Methodsmentioning
confidence: 99%
“…Treg-epithelial interactions were previously described. For example, crosstalk between Tregs and the intestinal or retinal epithelium is an important determinant of both immune tolerance and Treg proliferation (40)(41)(42). Type II alveolar epithelial cells (AECs) can present antigen to naive Tcells through the Class II major histocompatibility complex (MHC), and induce the proliferation of Tregs, in part through a transforming growth factor (TGF)-b-dependent mechanism (43).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, development and maintenance of this phenotype may further require IL-21, IL-23, or IL-1β, suggesting that there are several mechanisms that lead to the development of Th17 [9], [10]. We have previously shown that GECs express cytokines and receptors that influence the T cell response during H. pylori infection [11], [12]. In addition to GEC, we have also shown that CD90 + stromal cells (myofibroblasts and fibroblasts, MF) act as antigen presenting cells in the colon [13], [14].…”
Section: Introductionmentioning
confidence: 99%